A Brief Focus on SARS-CoV-2 Genomic Evolution and Vaccines - Annamaria Pratelli; Canio Buonavoglia (Pathogens, 2023)
Severe acute respiratory syndrome-coronavirus type 2 (SARS-CoV-2) emerged in a live animal market in the Hubei Province of Wuhan in China in late 2019 and was declared a pandemic by the World Health Organization (WHO) on 11 March 2020 [...]